Original PaperSocial aspects of chronic pain in patients with rheumatoid arthritis - Happach, Małgorzata; Moskalewicz, Bożena; Krzemińska-Dąbrowska, Izabela; Świerkocka, Katarzyna; Mańczak, Małgorzata (Reumatologia/Rheumatology, 2006)
Objectives: The study was designed to investigate social aspects of chronic pain and pain causing in patients with rheumatoid arthritis. Methods: 100 consecutive patients affected by RA treated in the outpatient department (min. 5, max. 15 years) were included in this study. All patients enrolled in the study answered a 40-minute interview with clinical and demographic data. We used the following measures: DAS 28 – disease activity, VAS – level of pain, and self-assessment of health status. Probands were also asked about coping with the disease and their opinion on doctor-patient relations. Results: On the day of investigation minor pain was reported by the majority of patients. Minor pain was not dependent on age. Nevertheless, every second patient experienced permanent long-lasting pain for a year before investigation. The majority of the group suffered from night pain, causing disturbance of sleep. Disease activity was average or high in the majority of the investigated group. Permanent, chronic pain causing disturbance of sleep reduces the level of self-assessment of health. Health status of more than half of the group has improved when compared to onset of disease. Improvement of function was two times more frequent than improvement of psychological self-assessment. Patients in direct contact with a specialist look for two important possibilities: to engage in dialogue with a doctor and to receive wide knowledge of disease and treatment. Conclusions: Significantly lower scores for improvement of psychological status in comparison with functional status after years of treatment indicate the significance of psycho-social aspects of rheumatoid arthritis. The two most important expectations of the patient in direct contact with a specialist are a partnership and wide knowledge of disease and treatment.